2020
DOI: 10.3389/fmolb.2020.574759
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of the N-Terminal Loop of PD-1 in Binding Process Between PD-1 and Nivolumab via Molecular Dynamics Simulation

Abstract: The blockade of immune checkpoints, such as programmed death receptor 1 (PD-1) and programmed death ligand 1 protein (PD-L1), is a promising therapeutic approach in cancer immunotherapy. Nivolumab, a humanized IgG4 antibody targeting PD-1, was approved by the US Food and Drug Administration for several cancers in 2014. Crystal structures of the nivolumab/PD-1 complex show that the epitope of PD-1 locates at the IgV domain (including the FG and BC loops) and the N-terminal loop. Although the N-terminal loop of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Given the structural similarity, Piezo1 also possess the 38-transmembrane-helix topology . The computing power of supercomputers enables molecular dynamics simulations of complex systems containing millions of atoms, thereby promoting the investigation of macromolecular structures. Chong and colleagues constructed the three-dimensional full-length Piezo1 structural model and confirmed that the trilobular membrane footprint of Piezo1 extends beyond the ion channel. Meanwhile, a combination of amino acid sequence data, available crystal structure, and molecular dynamics simulations facilitates the structural elucidation and biological function of the Piezo1 N-terminal.…”
Section: Structural Determination Of Piezo1mentioning
confidence: 99%
“…Given the structural similarity, Piezo1 also possess the 38-transmembrane-helix topology . The computing power of supercomputers enables molecular dynamics simulations of complex systems containing millions of atoms, thereby promoting the investigation of macromolecular structures. Chong and colleagues constructed the three-dimensional full-length Piezo1 structural model and confirmed that the trilobular membrane footprint of Piezo1 extends beyond the ion channel. Meanwhile, a combination of amino acid sequence data, available crystal structure, and molecular dynamics simulations facilitates the structural elucidation and biological function of the Piezo1 N-terminal.…”
Section: Structural Determination Of Piezo1mentioning
confidence: 99%
“…Nivolumab’s site may serve as a cryptic-allosteric site in PD-1 in the presence of N-loop. Liu et al and previous work from our lab highlighted the dominant role of N-loop in Nivolumab binding that could be a potential target zone on PD-1 to design anti-PD-1 inhibitors. , However, such grooves for small molecules or peptides are not defined in other mAb-bound PD-1 structures.…”
Section: Unraveling the Pd-1/mab Complexes To Locate The Hot-spots At...mentioning
confidence: 95%
“…Programmed cell death 1 (PD-1) has been proven to be a target in HCC in clinical trials. Nivolumab exhibits a high affinity and specific targeting to an epitope of PD-1 [27]. The risk assessment model in our study includes PD-1, which allows the model to more accurately identify patients who are sensitive to immunotherapy and evaluate patients' immune cell infiltration.…”
Section: Table 2 the Chi-square Test Of The Relation Between Risk Sco...mentioning
confidence: 99%
“…Our prediction model only included 3 immune-related gene pairs with 6 genes to assess both the prognosis and treatment sensitivity to immune and targeted therapy of HCC patients, and it was hard to include all genes reported. Actually, it contained 4 genes which were associated with the prognosis of HCC [20,23,24,27] and 2 genes which have been proved to be related to the prognosis of other tumors [25,26]. Third, we only used public datasets to construct the model and external validation, the practicality should be identified and the detailed relationship should be confirmed by further experiments.…”
Section: Table 2 the Chi-square Test Of The Relation Between Risk Sco...mentioning
confidence: 99%